Pengaruh Current Ratio, Total Asset Turnover, Debt To Asset Ratio dan Firm Size Terhadap Return On Asset (Pada Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar di BEI Tahun 2017-2023) - Ekawati, Yeni; Berliani, Kartika (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The purpose of this study is to investigate the effects of firm size, debt to asset ratio, current ratio, and total asset turnover on return on assets in the food and beverage manufacturing subsector listed on the IDX between 2017 and 2023. A quantitative method with a descriptive and verificative approach is the research methodology employed. Financial statements (annual reports) from the Food and Beverage Manufacturing Subsector's 2017–2023 annual reports, which are available on the IDX, provided the secondary data that was used. The t-test results demonstrated that Return on Asset is impacted by the Current Ratio. Return on Asset is impacted by total asset turnover. Firm size and the debt-to-asset ratio have little bearing on return on assets. The current ratio, total asset turn over, debt-to-asset ratio and firm size all significantly affect return on assets, according to the simultaneous test research.